Quality of Anticoagulation Management with Warfarin among Patients in Orotta National Referral Hospital, Asmara, Eritrea: A Retrospective Cross-Sectional Study - Natnael Russom; Saleh Idrisnur; Filipos Yohannes; Yuel Asefaw; Amanuel Tewelde (Patient Safety and Quality Improvement Journal)
Introduction:To analyze the quality of anticoagulation management with warfarin in Orotta National Referral Hospital, Asmara, Eritrea. Materials and Methods: A retrospective cross sectional study was conducted on patients aged 18 years and above who had received warfarin for Deep Vein Thrombosis and Valvular Heart Disease for at least 30 days. Data were collected by reviewing patients’ medical records. Time in Therapeutic Range (TTR) and International Normalized Ratio (INR) were used to analyze the quality and factors that affect the anticoagulation management. Results: Out of the 336 patients studied, 24.5% and 28.8% of patients, with Deep Vein Thrombosis (DVT) and Valvular Heart Diseases (VHD) respectively, had INR measurements within therapeutic range. The mean TTR was 25.1%, while the mean duration of INR monitoring for all patients was 40 days with a standard deviation of 43 days. The daily dose of warfarin was increased in 35.4% of participants following subtherapeutic INRs, and decreased in 50.6% following supratherapeutic INRs. No association was found between optimal TTR outcome and concomitantly used medications as well as comorbid conditions. However, the use of alternate dose regimen was found to be significantly associated with in-range (therapeutic) INR measurements. Conclusion: The study concluded that the quality of anticoagulation management with warfarin among patients in Orotta National Referral Hospital was suboptimal. This was demonstrated by low mean TTR, longer INR monitoring frequency and unsatisfactory measures taken to adjust warfarin dose after occurrences of non-therapeutic INRs.